The effect of the combination of split jump and short sprint training on flexibility in volleyball - I Ketut Yoda; Hendra Mashuri (Universitas Sriwijaya, 2023)
One of the elements of physical condition needed by volleyball players, especially the Volleyball Team of the Faculty of Sports and Health Undiksha is flexibility. This study aims to determine the effect of the combined plyometric split jump and short sprint training on the flexibility of the Faculty of Sports and Health Undiksha volleyball team. This research is quasi-experimental. The number of samples used was 40 people who were taken with a simple random technique. The data analysis technique used inferential statistics with hypothesis testing using paired T-test at a significance level of ?=0,05, assisted by SPSS.25. The results of data analysis show that there is a significant effect between